Prevalence and effect of pre-treatment drug resistance on the virological response to antiretroviral treatment initiated in HIV-infected children - a EuroCoord-CHAIN-EPPICC joint project - Ngo-Giang-Huong N. (2017)
© 2016 The Author(s). Background: Few studies have evaluated the impact of pre-treatment drug resistance (PDR) on response to combination antiretroviral treatment (cART) in children. The objective of this joint EuroCoord-CHAIN-EPPICC/PENTA project was to assess the prevalence of PDR mutations and their association with virological outcome in the first year of cART in children. Methods: HIV-infected children < 18 years initiating cART between 1998 and 2008 were included if having at least one genotypic resistance test prior to cART initiation. We used the World Health Organization 2009 resistance mutation list and Stanford algorithm to infer resistance to prescribed drugs. Time to virological failure (VF) was defined as the first of two consecutive HIV-RNA > 500 copies/mL after 6 months cART and was assessed by Cox proportional hazards models. All models were adjusted for baseline demographic, clinical, immunology and virology characteristics and calendar period of cART start and initial cART regimen. Results: Of 476 children, 88 % were vertically infected. At cART initiation, median (interquartile range) age was 6.6 years (2.1-10.1), CD4 cell count 297 cells/mm 3 (98-639), and HIV-RNA 5.2 log 10 copies/mL (4.7-5.7). Of 37 children (7.8 %, 95 % confidence interval (CI), 5.5-10.6) harboring a virus with ≥1 PDR mutations, 30 children had a virus resistant to ≥1 of the prescribed drugs. Overall, the cumulative Kaplan-Meier estimate for virological failure was 19.8 % (95 %CI, 16.4-23.9). Cumulative risk for VF tended to be higher among children harboring a virus with PDR and resistant to ≥1 drug prescribed than among those receiving fully active cART: 32.1 % (17.2-54.8) versus 19.4 % (15.9-23.6) (P = 0.095). In multivariable analysis, age was associated with a higher risk of VF with a 12 % reduced risk per additional year (HR 0.88; 95 %CI, 0.82-0.95; P < 0.001). Conclusions: PDR was not significantly associated with a higher risk of VF in children in the first year of cART. The risk of VF decreased by 12 % per additional year at treatment initiation which may be due to fading of PDR mutations over time. Lack of appropriate formulations, in particular for the younger age group, may be an important determinant of virological failure.